Parental Attachment Patterns Among Adolescents in an Islamic Boarding School: Gender Differences and Contextual Influences - Apriansyah, Apriansyah; Mariskha, Silvia Eka; Umaroh, Siti Khumaidatul (Unisia, 2025)
This study examines adolescent attachment among students in an Islamic boarding school, focusing on how parental bonds are maintained within a structured residential environment. The research aims to map attachment levels and explore gender differences in a setting shaped by religious values, communal routines, and prolonged separation from parents. Using a quantitative descriptive design, data were collected from 234 students through a validated attachment scale, and results were analyzed using descriptive statistics. The findings show that most students exhibit moderate attachment, indicating that boarding school life does not significantly erode parental bonds for the majority. A smaller proportion displays either low or high attachment, suggesting varied emotional experiences shaped by family dynamics and adaptation to residential life. Gender analysis reveals that male students cluster more consistently in the moderate range, whereas female students display greater variation across lower and higher attachment levels. These patterns align with research emphasizing the influence of cultural norms, gendered emotional tendencies, and peer relationships on adolescent attachment in communal educational settings. The study highlights the role of pesantren structures, such as shared routines, spiritual practices, and peer solidarity, in supporting emotional continuity despite physical distance from parents. The findings underscore the need for attachment-sensitive pastoral care and gender-responsive support within boarding schools and contribute new empirical evidence to the limited body of research on attachment in non-Western religious educational contexts.